2023
DOI: 10.1002/adfm.202300846
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Ferroelectric to colloidal Nanocrystals as a Generic Strategy to Engineer the Carrier Density Landscape

Abstract: The design of infrared nanocrystals‐based (NCs) photodiodes faces a major challenge related to the identification of barriers with a well‐suited band alignment or strategy to finely control the carrier density. Here, this study explores a general complementary approach where the carrier density control is achieved by coupling an NC layer to a ferroelectric material. The up‐and‐down change in ferroelectric polarization directly impacts the NC electronic structure, resulting in the formation of a lateral pn junc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The ferroelectric gate can retain nonvolatile polarization states, which are then used to electrostatically dope the adjacent semiconductor layer. This working principle is a cornerstone of the field of ferroelectronics, which encompasses various innovative device concepts such as ferroelectric memories, ferroelectric tunnel junctions, photodetectors, neuromorphic circuits, and ferroelectric FETs (FeFETs). In addition, disruptive circuit design concepts are being explored, where the internal polarization state of the FeFET serves as an input parameter for a new class of ferroelectric logic gates. , Recent advancements in the field have introduced ferroelectric van der Waals systems, which include van der Waals ferroelectric heterostructures with tunable interfacial physics, offering more possibilities as concern circuit design and device functionalities. ,,, However, the exploration of reconfigurable ferroelectric electronics and their potential for logic-in-memory remains mostly uncharted territory.…”
Section: Introductionmentioning
confidence: 99%
“…The ferroelectric gate can retain nonvolatile polarization states, which are then used to electrostatically dope the adjacent semiconductor layer. This working principle is a cornerstone of the field of ferroelectronics, which encompasses various innovative device concepts such as ferroelectric memories, ferroelectric tunnel junctions, photodetectors, neuromorphic circuits, and ferroelectric FETs (FeFETs). In addition, disruptive circuit design concepts are being explored, where the internal polarization state of the FeFET serves as an input parameter for a new class of ferroelectric logic gates. , Recent advancements in the field have introduced ferroelectric van der Waals systems, which include van der Waals ferroelectric heterostructures with tunable interfacial physics, offering more possibilities as concern circuit design and device functionalities. ,,, However, the exploration of reconfigurable ferroelectric electronics and their potential for logic-in-memory remains mostly uncharted territory.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we explore the use of photoemission microscopy as a tool to unveil in operando the electronic properties of the FPA. Recently, Cavallo et al have reported the use of such a method to probe the scalar energy landscape of NC-based field-effect transistors , and a photodiode . In particular, the method has been insightful in probing surface band bending at the NC semiconductor–electrode interface by providing direct evidence of the gate bias effect on the band alignment and unveiling the built-in potential of a diode .…”
Section: Introductionmentioning
confidence: 99%